![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) x - 2 = -6
x = -6 + 2
x = -4
2) -5 . x - ( -3 ) =13
-5 . x = 13 + ( -3 )
-5 . x = 10
x = 10 : ( -5 )
x = -2
![](https://rs.olm.vn/images/avt/0.png?1311)
1/(2.x-5)+17=6
=> 2x - 5 = -11
=> 2x = -6
=> x = 3
vậy_
2/10-2.(4-3x)=-4
=> 2(4 - 3x) = 14
=> 4 - 3x = 7
=> 3x = -3
=> x = -1
3/-12+3.(-x+7)=-18
=> 3(-x+7) = -6
=> -x+7 = -2
=> -x = -9
=> x = 9
4/24:(3.x-2)=-3
=> 3x - 2 = -8
=> 3x = -6
=> x = -2
5/-45:5.(-3-2.x)=3
=> 5(-3 - 2x) = -15
=> -3 - 2x = -3
=> - 2x = 0
=> x = 0
6/x.(x+7)=0
=> x = 0 hoặc x + 7 = 0
=> x = 0 hoặc x = -7
7/(x+12).(x-3)=0
=> x + 12 = 0 hoặc x - 3 = 0
=> x = -12 hoặc x = 3
8/(-x+5).(3-x)=0
=> -x + 5 = 0 hoặc 3 - x = 0
=> x = 5 hoặc x = 3
9/x.(2+x).(7-x)=0
=> x = 0 hoặc 2 + x = 0 hoặc 7 - x = 0
=> x = 0 hoặc x = -2 hoặc x = 7
10/(x-1).(x+2).(-x-3)=0
=> x - 1 = 0 hoặc x + 2 = 0 hoặc -x-3 = 0
=> x = 1 hoặc x = -2 hoặc x = -3
![](https://rs.olm.vn/images/avt/0.png?1311)
(2x - 7) + 17 = 6
=> 2x - 7 = 6 - 17
=> 2x - 7 = -11
=> 2x = -11 + 7
=> 2x = -4
=> x = -4 : 2
=> x = -2
+) 12 -2(3 - 3x)= -2
=> 2(3 - 3x) = 12 + 2
=> 2(3 - 3x) = 14
=> 3 - 3x = 14 : 2
=> 3 - 3x = 7
=> 3x = 3 - 7
=> 3x = -4
=> x = -4/3
\(\left(x+1\right)\left(x-3\right)=0\)
=> \(\orbr{\begin{cases}x+1=0\\x-3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=-1\\x=3\end{cases}}\)
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\text{ x . (x - 3) = 0}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x-3=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}\)
vậy_______
1 ) 5 - ( 10 - x ) = 7
10 - x = 5 - 7
10 - x = - 2
x = 10 - ( - 2 )
x = 12
Vậy x = 12
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,x.\left(x+7\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x+7=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=-7\end{cases}}}\)
\(2,\left(x+12\right).\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+12=0\\x-3=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-12\\x=3\end{cases}}}\)
\(3,\left(-x+5\right).\left(3-x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}-x+5=0\\3-x=0\end{cases}\Rightarrow\orbr{\begin{cases}-x=-5\\x=3\end{cases}\Rightarrow}\orbr{\begin{cases}x=5\\x=3\end{cases}}}\)
\(4,24:\left(3x-2\right)=-3\)
\(3x-2=-8\)
\(3x=-6\)
\(x=-2\)
\(5,-45:5\left(-3-2x\right)=3\)
\(5\left(-3-2x\right)=-15\)
\(-3-2x=-3\)
\(2x=0\)
\(x=0\)
\(6,x.\left(2+x\right)\left(7-x\right)=0\)
\(x=0\) hoặc \(\orbr{\begin{cases}2+x=0\\7-x=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-2\\x=7\end{cases}}}\)
\(7,\left(x-1\right)\left(x+2\right)\left(-x+3\right)=0\)
TH1: x-1=0 TH2 : x+2=0 TH3: -x+3=0
x=1 x=-2 -x=-3 => x=3
(x-40)(x-7)=0
=>x-40=0 hoặc x-7=0
=>x=40 hoặc x=7
tíc mình nha
1.\(\left(x-40\right)\left(x-7\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-40=0\\x-7=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=40\\x=7\end{cases}}\)
2. \(\left(x-12\right)\left(x+13\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-12=0\\x+13=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=12\\x=-13\end{cases}}\)
3. \(\left(2-x-4\right)\left(3x-9\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2-x-4=0\\3x-9=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-2\\x=3\end{cases}}\)